Industrial training report: Petronas Resource Centre / Muhammad Irfan Iqbal Abdul Hassan - Abdul Hassan, Muhammad Irfan Iqbal (Universiti Teknologi MARA, Negeri Sembilan, 2017)
I had undergone industrial training di Petronas Resource Centre, the headquarters (HQ) or main library or resource centre among libraries under this firm. The subject specialized of PRC HQ were included Oil and Gas, Energy, Drilling, Geology, Engineering, Chemistry, Information and Technology, Management, Economics, Leadership, Law and Government, Politics, Religion, and HSE (Health, Safety and Environment). I had learnt to be multitasking person as these tasks were given alternately with other jobs. The items in the archive storage need to be wellmanaged just as the items in Oil and Gas main location. The projects and programs should continuously be implemented and generated in order to foster the usage and utilization of PRC.